2020
DOI: 10.18502/ijph.v48i11.3513
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bimodal High-Voltage Monopulsed Current in the Treatment of Pressure Ulcer: A Systematic Review

Abstract: Background: We aimed to systematically evaluate the efficacy of high-voltage pulsed current (HVPC) in the treatment of pressure ulcer. Methods: We searched the databases of PubMed, Cochrane Library, Elsevier and EMBASE to identify randomized controlled studies on the application of HVPC in pressure ulcer treatment, up to January 2019. Two authors independently screened the literature according to the inclusion and exclusion criteria, extracted the data and evaluated the quality. RevMan 5.3 softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A total of 100 publications were excluded after reviewing the titles and abstracts, and the remaining 13 literature were further reviewed by reading the full text. Finally, ten eligible SRs/MAs were included 16–25 . The study selection process is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 100 publications were excluded after reviewing the titles and abstracts, and the remaining 13 literature were further reviewed by reading the full text. Finally, ten eligible SRs/MAs were included 16–25 . The study selection process is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with standard care alone or sham electrical stimulation, electrical stimulation resulted in a statistically significant improvement in healed rate 19,20,22,25 . Compared with standard care alone or sham electrical stimulation, electrical stimulation was reported by two reviews resulting in a statistically significant reduction in wound area 21,25 . Similarly, electrical stimulation resulted in a statistically significant improvement in daily percent decrease in ulcer size 19 and the proportion of ulcers healed 22,25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But in our works, all three outcomes have statistical differences between ES groups with the SWC groups or the sham groups. Girgis and Duarte (2018) and Zhang et al (2019) have investigated the HVMPC for treating PUs. Because both are lacking evidence‐based programme and other parameters' current, our study design was more prescriptive, and the focus was more extensive.…”
Section: Discussionmentioning
confidence: 99%
“…Well‐conducted conventional meta‐analyses of randomized controlled trials (RCTs) are accepted as the best‐quality evidence to inform clinical practice and health policy (Ge et al, 2018; Li et al, 2015). Recently, two systematic reviews and meta‐analyses (Girgis & Duarte, 2018; Zhang et al, 2019) were carried out to investigate the high‐voltage monophasic pulsed current (HVMPC) for treating PUs. They all confirmed that ES has positive effect on PU healing.…”
Section: Introductionmentioning
confidence: 99%